Assessment of slow blighting (Alternaria brassicae) resistance and yield in Indian mustard (Brassica juncea (L.) Czern. & Coss.) - KUMAR*, BRAJESH (Indian Phytopathology, 2008)
Field resistance/partial resistance to Alternaria blight (Alternaria brassicae) was assessed in nine genotypes of Indian mustard under field conditions. Three genotypes Viz. PR 8988, PR 9024 and Kranti exhibited partial resistance and had lowest per cent blight cover, apparent infection rate and AUDPC values. Size of spots was more robust parameter in identifying blighting resistance. Size of spots was positively & significantly correlated with maximum severity (r=0.985), leaf defoliation (r=0.934) and sporulation (r=0.985). The magnitude of correlation coefficients being greater than other parameters. The yield potential of the genotypes was negatively correlated with all blighting assessment parameters.